1989
DOI: 10.1111/j.1365-2796.1989.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure in anorexia nervosa with hypophosphataemia

Abstract: A 19-year-old woman with anorexia nervosa developed respiratory failure during parenteral nutrition. Serum phosphate concentration was low and the patient had several symptoms typical of hypophosphataemia. It is well known that parenteral refeeding may cause severe hypophosphataemia and this has earlier been described to cause respiratory failure in alcoholics and in patients with intestinal disease. This is, to our knowledge, however, the first reported case of respiratory failure in association with hypophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 1 publication
0
9
0
5
Order By: Relevance
“…Hypophosphatemia as a cause of respiratory failure and refractory weaning from the ventilator has been reported, albeit infrequently. Most patients had severe hypophosphatemia, and weaning from the ventilator was achieved after correction of hypophosphatemia [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Hypophosphatemia as a cause of respiratory failure and refractory weaning from the ventilator has been reported, albeit infrequently. Most patients had severe hypophosphatemia, and weaning from the ventilator was achieved after correction of hypophosphatemia [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…12 24-26 34 39 60 68 69 Children with protein energy undernutrition subjected to refeeding may suffer from dysphagia in addition to hypophosphataemia 18. In a semistarved male, hypophosphataemia due to alcohol poisoning caused dysphagia 70.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…Two mg phosphate/kg body weight over six hours is proposed as a suitable dose in the initial phase and serum phosphate will be restored within 36 hours 72. Acute respiratory failure occurs in hypophosphataemic patients with anorexia nervosa 12. The patient hypoventilates, in consequence of neuromuscular dysfunction.…”
Section: Treatment/preventionmentioning
confidence: 99%
“…It has also been suggested that the lack of phosphate buffering in the urine may contribute to the development of metabolic acidosis 10 . Respiratory failure secondary to the neuromuscular effects of hypophosphataemia can cause a respiratory acidosis 12,32 .…”
Section: Pathophysiology and Clinical Consequences Of Refeedingmentioning
confidence: 99%